2011
DOI: 10.1007/s00792-011-0395-y
|View full text |Cite
|
Sign up to set email alerts
|

Archaeal transcriptional regulation of the prokaryotic KdpFABC complex mediating K+ uptake in H. salinarum

Abstract: The genome of the halophilic archaeon Halobacterium salinarum encodes the high-affinity ATP-dependent K(+) uptake system Kdp. Previous studies have shown that the genes coding for the KdpFABC complex are arranged in a kdpFABCQ gene cluster together with an additional gene kdpQ. In bacteria, expression of the kdpFABC genes is generally regulated by the dedicated sensor kinase/response regulator pair KdpD/KdpE, which are absent in H. salinarum. Surprisingly, H. salinarum expresses the kdp genes in a manner which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
29
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(30 citation statements)
references
References 38 publications
1
29
0
Order By: Relevance
“…In our previous studies, we showed that expression of the kdpFABCQ operon, which encodes the K ϩ uptake system KdpFABC in H. salinarum, was strictly dependent on the K ϩ concentration in the growth medium (11,18). At extracellular K ϩ concentrations below 20 mM, the kdpFABCQ operon is moderately expressed, whereas expression significantly increased with concentrations below 250 M, with the highest expression level present at a 20 M concentration of external K ϩ .…”
mentioning
confidence: 96%
See 4 more Smart Citations
“…In our previous studies, we showed that expression of the kdpFABCQ operon, which encodes the K ϩ uptake system KdpFABC in H. salinarum, was strictly dependent on the K ϩ concentration in the growth medium (11,18). At extracellular K ϩ concentrations below 20 mM, the kdpFABCQ operon is moderately expressed, whereas expression significantly increased with concentrations below 250 M, with the highest expression level present at a 20 M concentration of external K ϩ .…”
mentioning
confidence: 96%
“…At this concentration, the cells ceased to grow due to the affinity limit of the KdpFABC complex for K ϩ . More-detailed studies of the kdp promoter (Pkdp) revealed an operator sequence upstream of the basal transcription elements as well as KdpQ acting as a coregulator stimulating expression under inducing conditions (11,18). Although the particular interplay of these regulatory components is still under investigation, further regulatory components within the kdpFABCQ coding region are clearly absent (11).…”
mentioning
confidence: 99%
See 3 more Smart Citations